Effects of short-term oxycodone maintenance on experimental pain responses in physically dependent opioid abusers - Coe, Marion A. (J Pain, 2017)
A common clinical problem with opioid analgesics is the loss of analgesic efficacy after repeated dosing; when this occurs, it is not clear what principles should guide providing effective analgesia among opioid-dependent individuals. This within-subject inpatient study aimed to determine if physically dependent opioid abusers (n=11) experience changes in oxycodone-induced analgesia during two oxycodone maintenance (30mg p.o./q.i.d.) phases: Initial Stabilization (Days 1–3) and after 6 weeks of Chronic Dosing. Six sessions (three each phase), measured Threshold, Tolerance & pain ratings for a Pressure Pain Test [PPT] and Cold Pressor Test [CPT]) after a single double-blind dose of oxycodone 30mg (Initial Stabilization) and 0, 30 & 60mg (Chronic Dosing) given in place of a scheduled maintenance dose. Physiologic and opioid agonist effects were assessed during Chronic Dosing sessions. There was no analgesic response to oxycodone 30mg. Oxycodone (60mg) produced a 25% increase in peak CPT Threshold compared to placebo, and significantly increased expired breath CO(2), miosis, and ratings of abuse liability measures. These data suggest that more than twice the acute oxycodone maintenance dose is needed to produce robust acute analgesia, though adverse effects (e.g. respiratory depression and abuse signals) may occur with lower doses.